THE VISUAL REACTION TIME DIFFERENCE BETWEEN UNDERWEIGHT, NORMAL AND OVERWEIGHT BODY MASS INDEX CATEGORIES AMONG STUDENT AT SARASWATI ELEMENTARY SCHOOL TABANAN - Putri, Ni Kadek Ira Maharani; Wibawa, Ari; Primayanti, I Dewa Ayu Inten Dwi (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 3 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT This study was to determine the difference of visual reaction time based on underweight, normal and overweight body mass index’s categories among student at Saraswati elementary school in Tabanan. This study design is a cross-sectional analytic study held on March 2017. Samples was selected using total sampling technique with totally 228 samples which divided into 3 groups based from their body mass index. Normality test using Kolmogorov-smirnov Test and homogeneity test using Levene’s Test had been done (p>0.05). Descriptive analytic show the visual reaction time in underweight BMI 569,4+50,08 ms, normal BMI 405,31+41,54 ms and overweight BMI 556,75+46,86 ms. Analysis using One Way ANOVA find out significant mean differences between group (p=0,000) Based on this study, conclude that underweight and overweight children had a longer visual reaction time than normal weight children in Saraswati Elementary School Tabanan. Keywords : Visual Reaction Time, Body Mass Index